School adolescents' knowledge concerning hepatitis C virus (HCV) - Lidia Sierpińska; Ewa Jankowska (Kazimierz Wielki University, 2017)
Introduction. Infection with hepatitis C virus (HCV) is a serious clinical, epidemiological and social problem inPoland.    Objective. The objective of the study was recognition of knowledge concerning HCV infection among adolescents attending post-secondary schools. Material and method. The study was conducted in 2016, among 106 school adolescents attending two post-secondary schools inRadom, by means of a questionnaire designed by the author and a standardized questionnaire according to the Polish Group of HCV Experts. Statistical analysis was performed using the software Statistica 10.0. Results. The majority of adolescents (84.5%) knew that HCV causes hepatitis C.  Boys more frequently than girls knew that the disease spreads by contact with infected blood (72.0% and 50.6%, respectively). Girls significantly more often than boys knew that approximately 700,000 people inPoland are infected with HCV (54.3% and 24.0%, respectively). According to 84.1% of respondents everyone is exposed to this infection.  Boys more often than girls (72.0% and 55.6%) correctly provided examples of situations in which the infection may occur. The majority of adolescents (88.5%) knew that the hepatitis C antibody (anti-HCV) blood test indicates whether the person has an infection. A half of the examined adolescents (50.9%) knew that there is currently no vaccine available to protect against hepatitis C, and that it is possible to cure the person infected with HCV. Conclusions. The level of adolescents' knowledge concerning HCV infection varied according to the demographic and social factors. School adolescents should be provided incentives for prophylaxis of infection and participation in prophylactic programmes, in order to limit the risk of contracting hepatitis C.